Motivation and Retention of Teachers in a Family Business in Education A Case Study from South Asia - Umair Ahmed; Waheed Ali Umrani; Ajay A. Chauhan (Faculty of Business, President University, 2018)
The case describes the professionalization, especially, the motivation and the commitment issues faced by Pioneers` School & College, a private family-run business in an emerging Asian economy of Pakistan. The case sheds light on the initiatives taken by the School’s Principal in this regard which resulted in the development of a unique teacher training program named, TeacherNurturing Program (TNP). At the core, the case focused on the training and development aspect of human resource management to motivate and retain the good teachers and improve quality of teaching standards. The case provides an opportunity for students to reflect upon the need for schools like Pioneers` to competitively act and introduce employee training and learning programsto maintain teachers’ motivation and commitment issues as well as to improve the school image through higher quality standards.